DNA hypomethylation traits define human regulatory T cells in cutaneous tissue and identify their blood recirculating counterparts - Beumer, Niklas; Imbusch, Charles; Kaufmann, Tamara; Schmidleithner, Lisa; Gütter, Kathrin; Stüve, Philipp; Marchel, Harriet; Weichenhan, Dieter; Bähr, Marion; Ruhland, Brigitte; Marini, Federico; Sanderink, Lieke; et al. (Nature immunology, 2025)
CD4+ regulatory T (Treg) cells in tissues play crucial immunoregulatory and regenerative roles. Despite their importance, the epigenetics and differentiation of human tissue Treg cells are incompletely understood. Here, we performed genome-wide DNA methylation analysis of human Treg cells from skin and blood and integrated these data into a multiomic framework, including chromatin accessibility and gene expression. This analysis identified programs that governed the tissue adaptation of skin Treg cells. We found that subfamilies of transposable elements represented a major constituent of the hypomethylated landscape in tissue Treg cells. Based on T cell antigen receptor sequence and DNA hypomethylation homologies, our data indicate that blood CCR8+ Treg cells contain recirculating human skin Treg cells. Conversely, differences in chromatin accessibility and gene expression suggest a certain reversal of the tissue adaptation program during recirculation. Our findings provide insights into the biology of human tissue Treg cells, which may help harness these cells for therapeutic purposes.
Gesehen am 01.12.2025